Changes in modus operandi of Islamic State terrorist attacks: review held by experts from Member States und Europol on 29 November and 1 December 2015 (Europol Public Information, 2016)
The recent attacks in Europe, carried out by Al-Qaeda (e.g. Paris, January 2015) and IS inspired or affiliated individuals and groups (e.g. Paris, November 2015, Brussels, March 2016), have increased concerns about possible future terrorist attacks by violent jihadist individuals and groups in EU Member States. This report presents an overview of the terrorist threat as perceived by the organisation and its main stakeholders, based on available information and expert knowledge. This report considers the terrorism threat from a law enforcement perspective and makes use of Europol’s unique access to information relating to terrorism and serious and organised crime. In preparation of the original report a meeting was organised with law enforcement experts of EU Member States. This meeting was held under the ‘Chatham House Rule’ and took place in The Hague in July 2016. The report has subsequently been updated to reflect the latest developments.